Microscopic evidence for nanoparticle-mediated growth of native gold in sulfide deposits at the Higashi–Aogashima Knoll Caldera hydrothermal field - Satoshi Okada; Junji Torimoto; Takahiro Kuribayashi; Toshiro Nagase; Akira Owada; Jun-ichiro Ishibashi; Akiko Makabe; Yutaro Takaya; Tatsuo Nozaki (PLoS ONE, 2025)
Gold (or electrum) in hydrothermal fluid precipitates directly from gold sulfide complex and/or partly via suspended nanoparticles. The hydrothermal fluid contains “invisible gold” that is atomically dispersed in sulfide minerals or as nanoparticles with a size of less than 10 nm. However, the contribution of these gold nanoparticles to the formation of native gold and its alloy with silver (electrum) remains unclear. The Higashi–Aogashima Knoll Caldera hydrothermal field, south of Tokyo, Japan, is an area of significant seafloor hydrothermal activity that is known for high-grade gold-containing minerals in sulfide-rich rocks. In this study, dry-polished thin sections were created to minimize sample damage and scanning and transmission electron microscopy were used to investigated the cross-sectional and three-dimensional morphologies of native gold grains in a sulfide-rich mound rock from the Central Cone site of the caldera. The surfaces of the gold grains comprised nanoparticles with sizes of 5–50 nm that were also attached to their periphery, which suggests that gold nanoparticles in deep-sea hydrothermal fluid were involved in the mineralization of the gold. In addition, the distribution of silver was uneven within the gold grains, which suggests that the gold precipitation comprised multiple stages at different temperatures that resulted in the post-deposition or secondary remobilization of silver.